An anaesthesiologists concern in a patient with posterior mediastinal mass - Gujaran, Rashmi D.; Latkar, Prajakta; Jain, Sulekha; Mehta, Hemant (International Journal of Research in Medical Sciences, 2021)
Large mediastinal masses may cause life threatening cardiorespiratory collapse depending on their location. An 18 years old female underwent ganglioneuroma excision. She had a 15×9.4×9.1 cm left sided cervico-thoracic mass surrounded by major blood vessels with mild encasement of left vertebral artery and left subclavian artery. After placing thoracic epidural, mask ventilation was confirmed with sevoflurane induction, and succinylcholine was given for intubation. Invasive monitoring of blood pressure was obtained with intravenous access in upper and lower limbs. For lung isolation, coopdech bronchial blocker was inserted into left main bronchus. Intraoperatively she was maintained on atracurium infusion, sevoflurane in oxygen air mixture. With a left hemiclamshell incision, mass was carefully separated from surrounding blood vessels and removed en bloc. After surgery patient was extubated and shifted to intensive care unit for observation. Patient was pain free and comfortable. Though our patients anaesthesia management and surgery was uneventful, we would like to discuss the potential complications that may arise with posterior mediastinal tumours as there are few articles discussing about the anaesthetic management of posterior mediastinal tumours.